In vitro growth of Coelogyne hybrid (Coelogyne pandurata x Coelogyne rumphii) on medium 2.4D and BAP - Ahmad Yunus; Sri Hartati; Samanhudi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2025)
Coelogyne is a genus of ornamental orchids renowned for its distinctive floral characteristics and high conservation and economic value, particularly Coelogyne pandurata, which is commonly referred to as a black orchid. Efforts in cultivating black orchids in vitro require media modification with the addition of growth regulators to optimize plant development. Growth regulators that can be used include auxins and cytokinins. This study evaluates the effects of 2.4D (2,4-Dichlorophenoxyacetic Acid ) and BAP on the in vitro growth and shoot proliferation of Coelogyne pandurata X Coelogyne rumphii hybrid seedlings. The experiment used a completely randomized design with two factors: 2,4-D and BAP, each with four concentration levels (0, 0.5, 1, and 1.5 ppm), resulting in 16 treatment combinations. The variables observed were the percentage of callus formation, callus color, shoot number, root number, leaf number, and plant length. The results showed that the optimal callus growth was achieved with a combination of 2,4-D at 0.5 ppm and BAP at 0.5 ppm, resulting in 100% callus formation. The 2,4-D treatment yields the optimum results in terms of leaf numbers (23.56) and plant height (2.15 cm), while the 1.5 ppm BAP treatment achieves the optimum results in terms of leaf numbers (31) and shoot numbers (22.39). Keywords: auxin; black orchid; callus; cytokinin; plant growth regulator